MAKNA KULTURAL RAMBUT GIMBAL ALAMI (BOK GEMPEL) DALAM SISTEM KEPERCAYAAN ORANG BALI - Setiawan, Bram (Humanis, 2016)
The phenomenon of natural dreads (bok gempel) in balinese people belief system is considered to contain the magical value. This research tries to reveal the meaning and impact of the phenomenon of dreads natural (bok gempel) against its owners, as well as the views of the public about such phenomena.     Research noted that natural dreads (bok gempel) in belief system the people of bali, generally believed to contain magic in its formation. An individual natural owner dreads (bok gempel) found various kinds of different experiences in the process of formation dreads (gempel ) it is in life. So this phenomenon eliciting profane, religious meaning and impact on the religious life and profane for its owners.